Methicillin resistant S. aureus and other resistances - Enright, Mark (Henry Stewart Talks, 2009)
Antibiotic resistance in hospitals, Antibiotic resistance in the community, The pre-antibiotic era, Penicillin, Tuberculosis, Streptomycin, Streptococcus pneumoniae, Multidrug resistant pneumococci, Staphylococcus aureus, Spread of MRSA, European and worldwide distribution of MRSA, Treatment of MRSA, The benefits of antibiotics, The extent of bacterial resistance in the UK, Causes of resistance, Antibiotic classes, The pyramids for antimicrobial use and selection for antimicrobial resistance, The threat, Why no new antibiotics?